Assessing the performance of different cover materials, in mitigation of evaporation from free water surfaces in Sulaimani Governorate / Iraq - Karim, Tariq Hama; Muhammad, Khalid Taiyb; Rasul, Roshn Mahmud (Sulaimani Journal for Pure and Applied Sciences, 2018)
In Iraqi Kurdistan region with intensive solar radiation and high vapor pressure deficit, particularly during the summer season, evaporative losses constitute a substantial amount of total stored water. To quantify and estimate evaporation losses besides testing the performance of some selected treatments for mitigating such losses a series of sequential experiments were implemented during some selected rainless months of 2015 and 2016 using evaporation pans. Each experiment was laid in completely randomized design. The treating materials encompassed indigenous and nonindigenous ones. Additionally, meteorological parameters were obtained for the test periods to relate pan evaporation to these parameters on one hand and to estimate pan coefficients from them, on the other hand. In this study the results were; 1) The small plastic balls as a covering materials (D =40 mm) offered the highest percent of evaporation reduction (60.81%) compared to those under large balls and under combination of these two sizes. 2) Comparison of three indigenous plant parts as shading cover, namely, Reed stems, Washingtonian fronds and Date palm mat, showed that the Date palm mat was the most effective material for reducing evaporation. 3) It was noticed that cardboard offered the highest performance compared with two other covering or shading materials (Cork disk and licorice branches) for reducing evaporation. 4) There was not a steady reduction in evaporation rate with an increase in monolayer application rate. The maximum reduction in evaporation rate occurred at an application rate of 0.226 g pan-1 Day-1 23.7%. 5) The order of preference of some screened treatment under the same atmospheric evaporation demand was: Small balls > Date palm mat > Monolayer > Control. 6). It was also noticed that the monolayer offered a higher performance during the field tests compared to that obtained during the pan evaporation experiments.
Keywords: Performace,Cover material; Mitigation; Evaporation; Water surface; Sulaimani